Optimizing Indonesian Tax Collection with Effectiveness and Efficiency Analysis through Transformation to Improve National Welfare - Priyono, Agus Puji; Nisa, Farhatun; Dwijayanti, Anggraeni (International Journal of Pertapsi, 2024)
This research uses a qualitative method with a descriptive analysis approach using secondary data obtained through observation and documentation to gain in-depth insight into the effectiveness and efficiency of tax collection in Indonesia for the 2018-2022 period and interviews with academics and practitioners in the field of taxation are also carried out for in-depth analysis of tax reform that supports the results of data on increases and decreases related to effectiveness and efficiency that have been carried out. The result is that from 2021 to 2022 the effectiveness in tax collection is declared effective, while from 2018 to 2020 it is ineffective where the lowest ratio occurs in 2019 at 0.84. During 2018-2022, the realization of DGT's budget expenditure is smaller than the budget plan set in the APBN, which shows that the use of DGT's budget expenditure is considered efficient where the variance value shows that the absorption of the planned budget is efficient. Various reforms to improve efficiency and effectiveness in tax policy, revenue supervision, and law enforcement in Indonesia such as the introduction of the functional position of tax extension officer for taxpayer education and consultation, Compliance Risk Management (CRM) supervision system is also implemented to map taxpayer risks, Tax policy includes digital tax and incentives and governance transformation to improve taxpayer compliance. Tax audit, comprehensively supervised ‘special audit’ aimed at improving work effectiveness.